FUNGAL INFECTION AND AFLATOXIN CONTAMINATION IN STORED NUTMEG (Myristica fragrans) KERNELS AT VARIOUS STAGES OF DELIVERY CHAIN IN NORTH SULAWESI PROVINCE - Okky S. Dharmaputra; Santi Ambarwati; Ina Retnowati; Nijma Nurfadila (BIOTROPIA, 2015)
Fragrant nutmeg (Myristica fragrans) is an important commodity widely used in food and pharmaceutical industries; therefore, its quality should be strictly monitored. The objectives of this research were to: (a) investigate the occurrence of fungi, including the presence of A. flavus and aflatoxin contamination in stored nutmeg kernels; (b) measure moisture content and percentage of damaged kernels; and (c) evaluate nutmeg kernels along the delivery chain. This study consisted of surveys, interviews, and sample collection along the delivery chain. The research was conducted in April–May 2013 in three regencies (North Minahasa, Siau Tagulandang Biaro (Sitaro), and Sangihe Talaud) and two cities (Bitung and Manado). A total of 76 nutmeg kernel samples were collected: 25 from farmers, 22 from collectors, and 29 from exporters. Results showed that the moisture content of nutmeg kernels collected from the North Sulawesi Province did not exceed the maximum moisture content limit set by the Indonesian National Standard (SNI), which is 10%. However, nutmeg kernels collected from farmers and collectors had a high percentage of physical damage. Aspergillus niger and Endomyces fibuliger were the dominant fungi found in samples from farmers and collectors, whereas Eurotium repens was predominantly associated with samples stored by exporters. Levels of aflatoxin B₁ and total aflatoxin in several samples collected from farmers and exporters were relatively high. A non-parametric statistical analysis showed that the delivery chain did not have a significant effect on moisture content, percentage of damaged kernels, total fungal population, or total aflatoxin content. This study suggests that improvements in postharvest handling practices performed by farmers, collectors, and exporters in North Sulawesi Province (North Minahasa, Sitaro, and Sangihe Talaud), Bitung, and Manado are necessary to minimize contamination of aflatoxin B₁ and total aflatoxin.